Quantification of immobilization-induced changes in human calf muscle using speed-of-sound ultrasound: An observational pilot study. Issue 11 (19th March 2021) - Ruby, Lisa; Sanabria, Sergio J.; Martini, Katharina; Frauenfelder, Thomas; Jukema, Gerrolt Nico; Goksel, Orcun; Rominger, Marga B.
Abstract : Abstract: Short-term immobilization leads to fatty muscular degeneration, which is associated with various negative health effects. Based on literature showing very high correlations between MRI Dixon fat fraction and Speed-of-Sound (SoS), we hypothesized that we can detect short-term-immobilization-induced differences in SoS. Both calves of 10 patients with a calf cast on one side for a mean duration of 41 ± 26 days were examined in relaxed position using a standard ultrasound machine. Calf perimeters were measured for both sides. A flat Plexiglas-reflector, placed vertically on the opposite side of the probe with the calf in-between, was used as a timing reference for SoS. SoS was both manually annotated by two readers and assessed by an automatic annotation algorithm. The thickness values of the subcutaneous fat and muscle layers were manually read from the B-mode images. Differences between the cast and non-cast calves were calculated with a paired t test. Correlation analysis of SoS and calf perimeter was performed using Pearson's correlation coefficient. Paired t test showed significant differences between the cast and non-cast side for both SoS ( P < .01) and leg perimeter ( P < .001). SoS was reduced with the number of days after cast installment ( r = −0.553, P = .097). No significant differences were found for muscle layer thickness, subcutaneous fat layer thickness, mean fat echo intensity, or mean muscle echo intensity. Short-term-immobilization led to a significant reduction in SoS in the cast calf compared to the healthy calf, indicating a potential role of SoS as a biomarker in detecting immobilization-induced fatty muscular degeneration not visible on B-mode ultrasound.